Mental health service acceptability for the armed forces veteran community. (15th June 2018) - Farrand, P; Jeffs, A; Bloomfield, T; Greenberg, N; Watkins, E; Mullan, E
Abstract: Background: Despite developments in mental health services for armed forces veterans and family members, barriers to access associated with poor levels of acceptability regarding service provision remain. Adapting a Step 2 mental health service based on low-intensity cognitive behavioural therapy (CBT) interventions to represent a familiar context and meet the needs of the armed forces veteran community may serve to enhance acceptability and reduce help-seeking barriers. Aims: To examine acceptability of a Step 2 low-intensity CBT mental health service adapted for armed forces veterans and family members provided by a UK Armed Forces charity. Methods: Qualitative study using individual semi-structured interviews with armed forces veterans and family members of those injured or becoming unwell while serving in the British Armed Forces. Data analysis was undertaken using thematic alongside disconfirming case analysis. Results: Adapting a Step 2 mental health service for armed forces veterans and family members enhanced acceptability and promoted help-seeking. Wider delivery characteristics associated with Step 2 mental health services within the Improving Access to Psychological Therapies (IAPT) programme also contributed to service acceptability. However, limitations of Step 2 mental health service provision were also identified. Conclusion: A Step 2 mental health service adapted for armed forces veterans and family members enhances acceptability and may potentially overcome help-seeking barriers. However, concerns remain regarding ways to accommodate the treatment of post-traumatic stress disorder and provide support for family members.